2019
DOI: 10.22555/ijelcs.v4i2.2757
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Programmed Learning and Metacognition: A Study on Experiential Learning Perspectives of Secondary School Teachers

Abstract: This research investigated the correlation between Programmed Learning and Metacognition of students in secondary schools of Karachi from the perspectives of secondary school teachers. Literature reported that poor academic performance, lack of interest and dis-connectivity with peers among the students was the result of poorly programmed instructions of their teachers. Literature also reported the positive correlation between Programmed Learning and the development of Metacognition of students along with qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, this issue is more severe in Balochistan, which is the largest province of Pakistan. This province lags behind in terms of progress and prosperity due to a weak education system (Mukhtar, et al, 2015;Ikram & Asim, 2019). Lack of qualified and experienced teachers, inadequate infrastructure, low enrollment rate, rampant poverty, cultural barriers, limited awareness, language barriers, and security issues are major challenges that exist even in the capital city of this province.…”
Section: Problem Statementmentioning
confidence: 99%
“…However, this issue is more severe in Balochistan, which is the largest province of Pakistan. This province lags behind in terms of progress and prosperity due to a weak education system (Mukhtar, et al, 2015;Ikram & Asim, 2019). Lack of qualified and experienced teachers, inadequate infrastructure, low enrollment rate, rampant poverty, cultural barriers, limited awareness, language barriers, and security issues are major challenges that exist even in the capital city of this province.…”
Section: Problem Statementmentioning
confidence: 99%
“…Programmed instruction materials can enhance the effectiveness of instruction as they have been thoroughly evaluated, reviewed, revised, and reproduced. Evaluation of this type of multimedia instruction has proven the importance of its application at different educational levels (Miloševic et al, 2016;Feeney, 2017;Ikram & Asim, 2019). However, the author found that studies on applying this type of e-courseware which is designed by programmed instruction method in primary schools over the past 5 years are relatively limited.…”
Section: Introductionmentioning
confidence: 99%